Recently released hybrids and varieties of pearl millet - Singh, S P; S, Mukesh Sankar; Singh, Nirupma; Satyavathi, C Tara (Indian Farming, 2019)
Pearl millet [Pennisetum glaucum (L.) R. Br.] is the staple food of poor and small farmers aswell as feed and fodder for livestock in the rainfed region of the country. Like some other C4 plantspecies, such as sorghum, maize, foxtail grass (Setaria spp) and switch grass, pearl millet adapts tomost hostile environments including, hot, dry, high light intensities and poor quality soils. Itrequires fewer inputs and is highly nutritious as food, feed and fodder. In India, pearl millet is thefourth most widely cultivated crop after wheat, rice and maize. Pearl millet is grown in 7.5million hectare during 2016-17. About 9.73 million tonnes of pearl millet was obtained duringthis period with a record productivity of 1,305 kg/ha. It is mainly grown in Rajasthan,Maharashtra, Gujarat, Uttar Pradesh and Haryana, and almost 90% acreage of pearl milletcomes from these states. It is mainly grown in kharif (June to October), although in certainpockets of Gujarat, Rajasthan and Uttar Pradesh, this crop is grown as summer crop (Februaryto May).